2023
DOI: 10.1002/hbm.26431
|View full text |Cite
|
Sign up to set email alerts
|

Modeling venous bias in resting state functional MRI metrics

Abstract: Resting‐state (rs) functional magnetic resonance imaging (fMRI) is used to detect low‐frequency fluctuations in the blood oxygen‐level dependent (BOLD) signal across brain regions. Correlations between temporal BOLD signal fluctuations are commonly used to infer functional connectivity. However, because BOLD is based on the dilution of deoxyhemoglobin, it is sensitive to veins of all sizes, and its amplitude is biased by draining veins. These biases affect local BOLD signal location and amplitude, and may also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 86 publications
(117 reference statements)
6
16
1
Order By: Relevance
“…A notable recent study by Huck et al found that the intravascular venous contributions to the rs-fMRI signal decreased with increasing vascular size (Huck et al, 2023). While we did not explicitly examine the effect of diameter, qualitative examination of our data do not corroborate such a finding.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A notable recent study by Huck et al found that the intravascular venous contributions to the rs-fMRI signal decreased with increasing vascular size (Huck et al, 2023). While we did not explicitly examine the effect of diameter, qualitative examination of our data do not corroborate such a finding.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Huck et al (Huck et al, 2023) suggested using high-order polynomials to model and remove both binned intravascular and binned extravascular venous bias. However, they found their model is insufficient to remove voxel-wise venous bias in rs-fMRI.…”
Section: Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations